AB0525 Safety and Efficiency of Low-Dose Interleukin-2 Treatment in Systemic Lupus Erythematosus. (9th June 2015) - He, J.; Zhang, X.; Yu, D.; Li, Z.-G.
Abstract : Background: Systemic lupus erythematosus (SLE) is an autoimmune disease characterized by loss of tolerance to nuclear self-antigens, production of pathogenic autoantibodies and damage to multiple organs. While corticosteroids and immunosuppressive agents have improved the outcome of patients, there remains a significant unmet need for safe and more effective treatments. Low-dose Interleukin-2 (IL-2) therapy has recently been shown effective to treat autoimmune disease. Objectives: To assess the safety and efficacy of low-dose IL-2 therapy in active SLE. Methods: We conducted a clinical trail on active SLE patients (NCT02084238 ). A total of 40 patients were enrolled. Patients with SLE Disease Activity Index (SLEDAI) scores ≥8 received three courses of low dose recombinant human IL-2 (1 million IU every second day for 2 weeks followed by a 2-week hiatus). The primary end point was the response rate at week 10. Both the safety and efficiency of IL-2 therapy were evaluated. Results: Total 36 patients (36/40, 90%) achieved an SLE Responder Index (SRI) improvement at week 6. No patients demonstrated high grad adverse events; mild injection-site reaction was observed in 5 patients (5/40, 12.5%). Better response was seen in patients with skin involvement (erythema, photo sensibility, Rdynolds, vasculitis), hematologic abnormities (leukopenia, Thrombocytopenia and anemia) and disease-related fever. Patients showed the improvement of major laboratory indicators, including reduced anti-dsDNA autoantibody titres and 24-hour proteinuria, and increased levels of the complement proteins C3 and C4. Immunological analysis showed significant increase of Treg cells and decrease of effector helper T cells after the therapy. Conclusions: Our results showed that low-dose IL-2 therapy in active SLE were safe and achieved satisfactory efficacy with increasing Treg and decreasing effector helper T cells. References: Jing He, Louis M. Tsai, Yew Ann Leong, Xin Hu, Cindy S. Ma, Nina Chevalier, Xiaolin Sun, Kirsten Vandenberg, Steve Rockman, Yan Ding, Lei Zhu, Wei Wei, Changqi Wang, Alexander Karnowski, Gabrielle T. Belz, Joanna R. Ghali, Matthew C. Cook, D. Sean Riminton, André Veillette, Pamela L. Schwartzberg, Fabienne Mackay, Robert Brink, Stuart G. Tangye, Carola G. Vinuesa, Charles R. Mackay, Zhanguo Li, * and Di Yu, * Circulating Precursor CCR7loPD-1hi CXCR5+ CD4+ T Cells Indicate Tfh Cell Activity and Promote Antibody Responses upon Antigen Reexposure. Immunity, 2013, 39(4), 770-781 Disclosure of Interest: None declared